Part-Time Faculty: Student Perceptions and Experiences - Lundy, Katherina L.P.; Warme, Barbara D. (Canadian Journal of Higher Education, 1989)
Educators and higher education researchers have speculated that the presence of part-time faculty in universities must have a negative impact on students' learning experience. The research reported in this article has yielded no evidence in support of this view. Students tend to be either unaware of, or indifferent toward, differences between part-time and full-time status.